2019
DOI: 10.1039/c9nr07171g
|View full text |Cite
|
Sign up to set email alerts
|

Tetrahedral framework nucleic acids prevent retina ischemia-reperfusion injury from oxidative stress via activating the Akt/Nrf2 pathway

Abstract: Retinal ischemia-reperfusion (I/R) injuries are involved in the universal pathological processes of many ophthalmic diseases, including glaucoma, diabetic retinopathy, and retinal arterial occlusion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
49
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 67 publications
(55 citation statements)
references
References 43 publications
6
49
0
Order By: Relevance
“… 23 25 Moreover, cellular uptake is the key to the various effects of tFNAs on wound healing. 26 , 28 Therefore, after we successfully prepared tFNA nanostructures of an appropriate size and with a stable zeta potential, we demonstrated that tFNAs could be taken up in abundance by these two types of cells.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“… 23 25 Moreover, cellular uptake is the key to the various effects of tFNAs on wound healing. 26 , 28 Therefore, after we successfully prepared tFNA nanostructures of an appropriate size and with a stable zeta potential, we demonstrated that tFNAs could be taken up in abundance by these two types of cells.…”
Section: Discussionmentioning
confidence: 92%
“… 27 30 In addition, tFNAs may influence different signaling pathways, such as the Wnt pathway and the Nrf2 pathway. 27 , 28 However, to the best of our knowledge, there have been few reports regarding nucleic-acid nanophase materials that directly affect the skin wound healing process without delivery assistance. In this study, we focused on evaluating the effects of tFNAs on keratinocytes (HaCaT cell line) and fibroblasts(HSF cell line) in vitro and in rat wound models in vivo.…”
Section: Introductionmentioning
confidence: 99%
“…[ 20–24 ] In our early exploration in the prevention and treatment of various eye diseases, tFNAs have been proved to act a positive part as drugs in repairing corneal injury and the anti‐oxidative stress of RGCs. [ 25,26 ] Furthermore, our previous studies have shown that tFNAs can exert neuroprotective influence in the Alzheimer's disease in vitro model. [ 27 ] Hence, in this work, tFNAs were selected as the carrier for miR‐22‐3p to synthesize a complex of tFNAs and miRNAs (tFNAs‐miR22).…”
Section: Introductionmentioning
confidence: 99%
“…The search for new biologically active molecules for the prevention and correction of retinal ischemia-reperfusion is one of the tasks of current ocular pharmacology [16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%